The Impact of the Upgrading of the Industrial Structure on the Urban Employee Basic Medical Insurance Fund: An Empirical Study in China - Zheng M; Zhu J (Dove Medical Press, 2021)
Meng Zheng,1,2 Junli Zhu1,2 1School of Public Health, Capital Medical University, Beijing, People’s Republic of China; 2Research Center for Capital Health Management and Policy, Beijing, People’s Republic of ChinaCorrespondence: Junli ZhuDepartment of Health Management and Policy, School of Public Health, Capital Medical University, No. 10, Xitou Road, Youanmen Wai, Beijing, 100069, People’s Republic of ChinaTel +86 18701515093Fax +86 01083911578Email smallying@126.comBackground: During the transformation of economy to a high-quality level in China, industrial restructuring and upgrading have played an important role. The upgrading of the industrial structure has affected not only the development in society and economy but also other fields, thereby having great impact on social security. In recent years, with the aging of the population and economic development, the social medical insurance fund is undertaking more payment pressure. However, the existing research rarely focuses on the impact of industrial structure upgrading on medical insurance.Objective: The main aim of this study was to analyze the impact of the upgrading of industrial structure on the income and expenditure of the urban employee basic medical insurance fund.Methods: China’s provincial panel data from 2007 to 2018, collected by the National Bureau of Statistics of China, were used to establish a panel regression model in order to investigate the impact of the upgrading of the industrial structure on the income and expenditure of the urban employee basic medical insurance fund.Results: The research showed that the upgrading of the industrial structure, in combination with the internal upgrading in the tertiary industry, had a positive impact on the income and expenditure of the urban employee basic medical insurance fund and that there were regional differences. The simple upgrading of the three major industries had no effect on the income or expenditure of the urban employee basic medical insurance fund. In addition to the upgrading of industrial structure, other factors such as the average salary of employed persons in urban units, the proportion of retirees among all insured persons in urban employee basic medical insurance and the expenditure of urban employee basic medical insurance were also found to have impact on the income of urban employee basic medical insurance. Moreover, the expenditure of urban employee basic medical insurance was associated with the proportion of retirees among all insured persons in urban employee basic medical insurance, GDP and an aging population.Conclusion: In the context of the upgrading of the industrial structure, measures such as strengthening employment and income security, delaying retirement, adjusting birth policy, strengthening the scientific management of personal accounts and accurately positioning the regional industrial structure were suggested to be adopted in order to minimize the payment pressures on the urban employee basic medical insurance fund.Keywords: industrial structure upgrading, urban employee basic medical insurance, panel regression model, employment structure